2021
DOI: 10.1016/j.cgh.2020.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Peak Concentrations of Ustekinumab After Intravenous Induction Therapy Identify Patients With Crohn’s Disease Likely to Achieve Endoscopic and Biochemical Remission

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 24 publications
(34 reference statements)
0
33
0
Order By: Relevance
“…Finally, there are multiple factors that can influence UST trough levels in an individual patient. Higher UST exposure can be expected in patients with markers of a more limited inflammatory burden and less aggressive disease like higher albumin, lower baseline C-reactive protein, lower fecal calprotectin and no previous exposure to biological therapy (88,89). In summary, UST concentrations have been associated with improved results in refractory patients with CD, demonstrating a favorable exposure-outcome relationship.…”
Section: Pharmacokineticsmentioning
confidence: 93%
See 1 more Smart Citation
“…Finally, there are multiple factors that can influence UST trough levels in an individual patient. Higher UST exposure can be expected in patients with markers of a more limited inflammatory burden and less aggressive disease like higher albumin, lower baseline C-reactive protein, lower fecal calprotectin and no previous exposure to biological therapy (88,89). In summary, UST concentrations have been associated with improved results in refractory patients with CD, demonstrating a favorable exposure-outcome relationship.…”
Section: Pharmacokineticsmentioning
confidence: 93%
“…On the other hand, evidence regarding early UST concentrations and prediction of later outcomes in CD is limited. Recently, a prospective observational study by Hanzel et al found that 6 of 13 patients (46%) with peak concentrations above 105 µg/mL achieved endoscopic remission, compared with only 7% among those with peak concentrations below 88 mg/mL (88). These authors concluded that therapeutic drug monitoring as early as during the first 2 weeks of initiation of UST might help stratify patients according to the probability of achieving treatment outcomes at 6 months.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…It has demonstrated very good effectiveness in CD patients, who previously failed treatment with anti-TNF [64]. Recent studies have indicated that serum concentrations of ustekinumab in patients with CD, following an hour after intravenous infusion, can be utilized for the further optimization of the treatment [65]. Van den Berghe et al [66], intended to develop and subsequently validate a DBS method, for the identification of the most appropriate time points to determine the ustekinumab concentrations, for the prediction of the treatment outcome, as well as for the investigation of its PK profile.…”
Section: Othersmentioning
confidence: 99%
“…Pharmaceutics 2021, 13 Ustekinumab is an IgG1κ monoclonal antibody that binds with high affinity to the p40 subunit shared by interleukin 12 (IL12) and interleukin 23 (IL23) [5]. Standard dosing with weight-based intravenous induction followed by 90 mg subcutaneous injections every 8 weeks is not effective for all patients, with real-world studies reporting that only up to one half of the patients achieve clinical remission, and up to 25% of patients achieve endoscopic remission [6][7][8][9][10][11]. The exposure-response relationship between peak ustekinumab serum concentration after the induction dose and endoscopic remission at 24 weeks suggests that a subset of patients not responding to conventional dosing may benefit from dose escalation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Standard dosing with weight-based intravenous induction followed by 90 mg subcutaneous injections every 8 weeks is not effective for all patients, with real-world studies reporting that only up to one half of the patients achieve clinical remission, and up to 25% of patients achieve endoscopic remission [6][7][8][9][10][11]. The exposure-response relationship between peak ustekinumab serum concentration after the induction dose and endoscopic remission at 24 weeks suggests that a subset of patients not responding to conventional dosing may benefit from dose escalation [11]. Recent real-world studies assessing off-label intensified maintenance therapy with 90 mg administered every four weeks in patients with insufficient response have shown favorable rates of clinical, biochemical and endoscopic remission [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%